Fast fabrication of micron-sized Janus particles with controlled morphology via seed-swelling photoinitiated polymerization and their application in Cu (II) ion removal. (16th January 2023) - Jia, Shicong; Wang, Hongwei; Tang, Ruizhi; Ma, Shujuan; Gong, Bolin; Ou, Junjie
Abstract: At present, most of Janus particle with different shapes were synthesized via seeded emulsion thermal-initiated polymerization. Herein, a novel and simple strategy of seed-swelling photoinitiated polymerization was proposed to fabricate Janus particles, in which noncrosslinked polystyrene seed was swelled via absorbing an oil phase consisting of glycidyl methacrylate (GMA) as functional monomer, dipentaerythritol pentaacrylate (DPEPA) as crosslinker and different organic solvents. Several parameters such as molar ratio of monomer and crosslinker, irradiation time of UV light, the types of porogenic reagents and the composition of aqueous phase were investigated. Numerous liquid droplets merged into multiple protrusions, and further immobilized onto the surface of seed particle. Subsequently, half raspberry-like particle was finally generated with low molar ratio of monomer and crosslinker, while both dumbbell-like and egg-like Janus particles were acquired in higher molar ratio of monomer and crosslinker. These Janus particles were synthesized via "green" process owning to fast and simple characters. After modification via surface-initiated atom transfer radical polymerization (SI-ATRP) and amination, the as-synthesized Janus@polyAN-TEPA was utilized in the adsorption of Cu (Ⅱ) ion and the maximum adsorption reached 132 mg g −1 . As a result, the Janus particles demonstrated excellent capacity on absorption of Cu (Ⅱ) ion, and it is promising to utilize the Janus particle in the fields of separation and enrichment. Graphical abstract: Image 1 Highlights: A novel strategy of seed-swelling photoinitiated polymerization was proposed to fabricate Janus particles. Three Janus particles of half raspberry-like, dumbbell-like and egg-like were synthesized by adjusting several reaction parameters. Whole preparation process of Janus particles was carried out at room temperature, and the polymerization process was fast. The Janus particle demonstrated excellent capacity on absorption of Cu (Ⅱ) ion after modification via ATRP technique.